What Can Professional Scientific Societies Do to Improve Diversity, Equity, and Inclusion: A Case Study of the American Elasmobranch Society - Shiffman, David S.; Arguedas Álvarez, Triana; Bangley, Charles W.; Boyt, Reilly; Côté, Isabelle M.; Daly-Engel, Toby S.; Davis, Alexandra C. D.; Gaskins, Leo C.; Graham, Jasmin; Graham, R. T.; Johri, Shaili; Macdonald, Catherine C.; et al. (Frontiers in Education, 2022)
Scientific professional societies are reviewing diversity, equity, and inclusion (DEI) practices and policies in response to recent calls for much-needed change. Organizations like scientific professional societies contribute to establishing disciplinary norms, and can influence the diversity of disciplinary workforces in multiple ways through both action and inaction. This paper examines these issues using the American Elasmobranch Society, a medium-sized professional scientific society, as a case study. It consists of three parts: 1) An analysis of the demographics of AES members, leaders, and award winners; 2) Evaluation of a diversity initiative created by the society which includes a survey of program alumni focusing potential improvements to the program; and 3) A synthesis of recommendations of steps that AES and similarly-sized societies can take to better support DEI goals. AES’s membership in recent years is more than half women, but 71.5% of all leadership positions in the Society’s history (including all but two Presidents) have been held by men since the society was founded in1983. AES’s membership has significantly fewer Black/African-American members than the US scientific workforce overall, with just one member out of over 400 identifying as Black in 2019, and 86.6% of Society leadership positions have been held by white-presenting members. The Society’s diversity initiative has led to some limited professional benefits for awardees, and could benefit from additional resources and support to enact suggested expansions and improvements. We provide a series of actionable recommendations that will make the annual meetings of societies like AES, and the field of chondrichthyan science, safer and more inclusive.